Calcaneal skeletal traction versus elastic intramedullary nailing of displaced tibial shaft fractures in children. Issue 4 (April 2021) - Zeng, Shuaidan; Deng, Hansheng; Zhu, Tianfeng; Han, Shuai; Xiong, Zhu; Tang, Shengping
Highlight: The largest and first study to compare EIN with CST for displaced tibial shaft fracture in a Chinese population. The CST procedure had faster surgical time, cast duration, and longer hospitalization. Patients in EIN group began exercising and endured weight-bearing earlier. The CST provided better results of coronal correction than EIN. Moreover, CST patients had less malalignment (> 5°) in complications. The characteristics of the patient and fracture, the individual's situation and expectation should be considered when choosing the best approach. Abstract: Background: The objective of this study was to compare the outcomes and complications of patients who underwent either the calcaneal skeletal traction (CST) or the elastic intramedullary nails (EIN) procedure. Methods: We retrospectively reviewed data of patients who underwent EIN or CST surgery for tibia shaft fracture at our center from 2013 to 2018. The patient demographics, fracture characteristics, radiographic information, length of hospital stay, and medical expenses were recorded. All patients were clinically followed-up until they started to walk or for at least 6 months. The treatment outcomes and postoperative complications of the two procedures were compared. Results: Overall, 186 patients who underwent EIN and CST were included in the study. The EIN patients had more low-energy mechanism of injury. In radiographic evaluation, significant differences were observed in distributions of fracture classification and location. Moreover, associated fibula fractures were higher in the EIN group than in the CST group. The CST procedure had faster surgical time, cast duration and lower expenses, and longer hospitalization time. Although they required more clinical visits, patients in the EIN group began exercising and endured weight-bearing earlier than those in the CST group. The average time for bone healing was 68.5 days in the EIN group, and 69.6 days in the CST group. However, the CST provided slight better results of coronal correction than EIN. Moreover, CST patients had less malalignment (> 5°) in complications. None had delay union, nonunion, and shortening over 10 mm at final assessment. Conclusions: Both EIN and CST patients showed similar treatment outcomes. Hence, not only the characteristics of the patient and fracture, but also the individual's situation and expectation should be considered when choosing the best approach.